Школьный друг - Зверев Сергей Иванович (Спецназ, 2014)
Экземпляры: ф.1 (20240130) / Инвентарный номер: 64275 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: З-43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44